2016
DOI: 10.1152/japplphysiol.00620.2016
|View full text |Cite
|
Sign up to set email alerts
|

Postinjury biomechanics of Achilles tendon vary by sex and hormone status

Abstract: Achilles tendon ruptures are common injuries. Sex differences are present in mechanical properties of uninjured Achilles tendon, but it remains unknown if these differences extend to tendon healing. We hypothesized that ovariectomized females (OVX) and males would exhibit inferior postinjury tendon properties compared with females. Male, female, and OVX Sprague-Dawley rats (n = 32/group) underwent acclimation and treadmill training before blunt transection of the Achilles tendon midsubstance. Injured hindlimbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Animals (n=12–16/group) were acclimated to an instrumented walkway, and spatial, temporal, and kinetic parameters were quantified during autonomous locomotion as previously described (Fryhofer et al, 2016). Briefly, maximum ground reaction forces (medial/lateral, braking, propulsion, vertical) were calculated following isolation of the hindlimb on either one of two six degree-of-freedom force plates and reported as percent of animal body weight (%BW).…”
Section: Methodsmentioning
confidence: 99%
“…Animals (n=12–16/group) were acclimated to an instrumented walkway, and spatial, temporal, and kinetic parameters were quantified during autonomous locomotion as previously described (Fryhofer et al, 2016). Briefly, maximum ground reaction forces (medial/lateral, braking, propulsion, vertical) were calculated following isolation of the hindlimb on either one of two six degree-of-freedom force plates and reported as percent of animal body weight (%BW).…”
Section: Methodsmentioning
confidence: 99%
“…We used an established animal model of Achilles tendon transection and post-injury hind limb immobilization (Freedman et al, 2016a; Freedman et al, 2016b; Fryhofer et al, 2016) to carefully control the activity paradigm of animals for longitudinal functional and tissue-level follow-up. As most studies examining long-term follow-up in Achilles tendon healing have been completed in humans, this work provides fundamental insight into the tissue-level mechanical and histological changes that exist following injury.…”
Section: Discussionmentioning
confidence: 99%
“…Ground reaction forces and temporal patterns for the right hind limb were used to evaluate active limb function prior to surgery, and at 4-, 6-, 10-, and 16-weeks post-injury (Freedman et al, 2016a; Freedman et al, 2016b; Fryhofer et al, 2016). Briefly, animals ambulated across an instrumented walkway containing load/torque cells and a camera, and all animals were acclimated four times prior to formal data collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies on humans has shown that women's response to exercise in Achilles tendons is differently compared to men, and might reduce their ability to adapt to exercise (7). Additionally, female rats seem to improve their mechanical properties faster in healing Achilles tendons compared to males and ovariectomized females (24). We have only studied female rats and that might be a limitation of our findings, as there seems to be a difference between genders.…”
Section: Comparison With Other Studiesmentioning
confidence: 84%